Controlling the growth of vertically aligned single walled carbon nanotubes from ethanol for electrochemical supercapacitor application - Asyadi Azam, Mohd; Mohamed, Mohd Ambri; Shikoh, Eiji; Fujiwara, Akihiko; Shimoda, Tatsuya (2010)
Here, we report on the growth of VA-SWCNTs using the ACCVD technique. Al2O3-supported Co catalyst and high purity ethanol (carbon feedstock) were used for the growth process. Both Al layer and Co thin-films were deposited using an electron beam evaporator. The Al layer of 20 nm nominal thickness was manually oxidized before the deposition of 0.5 nm Co. The CNT growth was optimized using Si/SiO2 substrates, and the selected growth parameter was applied to each conducting substrate such as Inconel 600, Inconel 601, Si, and SUS 310S. In order to understand the mechanism of the CNT growth, synthesis of the catalyst nanoparticles and their structural characterization before CVD growth were carried out using atomic force microscope (AFM), scanning electron microscope (SEM), and x-ray diffraction (XRD). The properties of the as-grown CNTs were mainly characterized using Raman spectroscopy and SEM.